Evolution of Autonomy in Idiopathic Non-Toxic Goiter, Evaluated by Regional Suppressibility of 99mTc-Uptake and TSH Response to TRH - Dige-Petersen, H.; Clemmensen, O. J.; Hummer, L. (Nuklearmedizin - NuclearMedicine, 1976)
Seventeen euthyroid patients with non-toxic goiter were studied, 7 had diffuse goiters and 10 had nodular goiters. The TSH response to TRH and the 99mTc-uptake were measured before and after T3 suppression. The uptake, measured with a gamma camera, was calculated for the whole gland and for a maximum of 6 regions within the thyroid gland.The suppressibility of 99mTc-uptake (percent change of uptake) ranged from 0 to 95%, it was significantly greater in patients with diffuse than in those with nodular goiters, and was alike in nodular and inter-nodular tissue. The patients with diffuse goiter were significantly younger than those with nodular goiter. Abolished TSH response to TRH was seen in 2 patients with negative T3 suppression tests. In another 2 patients impaired TSH response was associated with impaired suppressibility. In 13 patients with normal TRH tests, the suppression of uptake was normal in 8 and subnormal in 5.The results suggest that nodularity and functional autonomy may develop in non-toxic goiters. In some of these goiters the mass of autonomous tissue may be large enough to cause negative TRH tests, probably indicating hypersecretion of thyroid hormones, although not necessarily above the normal range.